Insurance Against Longevity Risk in a Pension System the Case Study of Poland - Szczepański, Marek (Olsztyn Economic Journal, 2015)
Life expectancy has been rapidly increasing and remains uncertain in all OECD countries, including Poland. One of the many economic and social consequences of this process is the increase of the longevity risk in social security systems. This article focuses on the issues of managing longevity risk in the pension system in Poland, in particular - the construction of public and supplementary pension systems and its ability to adapt to the challenges associated with longevity risk. Particular attention has been paid to the analysis of public structures and supplementary pension schemes in the phase of payment of benefits (decumulation). The research work, of which the results are presented in the article, is based on literature studies, comparative analysis, statistical analysis; as well as descriptive and explanatory methods. Also, a model of the two stages of pension risk created by T. Szumlicz has been used. The author argues that both the public pension systems as well as the supplementary pension schemes in Poland do not secure adequate protection against the risk of longevity. While in the public retirement system, the aggregate longevity risk exists, and the participants of additional pension systems are exposed to individual longevity risk. The limitation of these risks requires significant structural changes both in the public and in the additional pension schemes in Poland.